2015
DOI: 10.4238/2015.december.8.15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity and population structure of oil palm (Elaeis guineensis) from China and Malaysia based on species-specific simple sequence repeat markers

Abstract: ABSTRACT. Genetic diversity and patterns of population structure of the 94 oil palm lines were investigated using species-specific simple sequence repeat (SSR) markers. We designed primers for 63 SSR loci based on their flanking sequences and conducted amplification in 94 oil palm DNA samples. The amplification result showed that a relatively high level of genetic diversity was observed between oil palm individuals according a set of 21 polymorphic microsatellite loci. The observed heterozygosity (H o ) was 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
9
1
1
Order By: Relevance
“…One interesting thing was that, despite of evaluating only seven RAMs over 51 palm genotypes, the He value between 0.35 and 0.98 was higher than those reported by Ting et al (2010) using 15 SSR markers (Ho and He values of 0.40 and 0.44, respectively), or those reported by Zhou et al (2015) with 21 polymorphic microsatellite loci (Ho values of 0.37 and 0.40, with an average of 0.39). Also, Rocha-Salavarrieta et al (2007) found a He value of 0.515 when assessing the genetic diversity of 72 oil palm genotypes from Angola with 16 microsatellite loci.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…One interesting thing was that, despite of evaluating only seven RAMs over 51 palm genotypes, the He value between 0.35 and 0.98 was higher than those reported by Ting et al (2010) using 15 SSR markers (Ho and He values of 0.40 and 0.44, respectively), or those reported by Zhou et al (2015) with 21 polymorphic microsatellite loci (Ho values of 0.37 and 0.40, with an average of 0.39). Also, Rocha-Salavarrieta et al (2007) found a He value of 0.515 when assessing the genetic diversity of 72 oil palm genotypes from Angola with 16 microsatellite loci.…”
Section: Resultsmentioning
confidence: 70%
“…Arias and Rocha (2004) evaluated E. guineensis and E. oleifera genotypes from Cenipalma's germplasm bank with RAPD, SSR and AFLP markers for selecting resistant or tolerant materials to this disease, and Villegas et al (2000) evaluated the genetic diversity of 126 genotypes from the Promociones Agropecuarias Monterrey Plantation with 12 RAPD. Some molecular markers and protein markers have also been used to investigate genetic diversity in oil palm germplasm such as: Restriction Fragment Length Polymorphism (RFLP) of ribosomal DNA (Rajanaidu et al 1989;Jack et al 1995;Shah et al 1993); random amplified polymorphic DNA (RAPD) (Shah et al 1994;Sathish and Mohankumar 2007;Ochoa et al 1997;Villegas et al 2000); microsatellite markers or SSR (Chavarro et al 2016;Arias et al 2014;Zhou et al 2015); RFLP using cDNA probes (Singh et al 2008); amplified fragment length polymorphism (AFLP) (Galeano 2005); and isoenzyme markers (Purba et al 2000;Choong et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies based on a limited amount of molecular markers (14 polymorphic loci out of 11 enzymatic systems, 37 restriction fragment length polymorphisms [RFLPs], 96 random amplified polymorphic DNA markers [RAPDs], and 19 simple sequence repeats [SSRs], respectively) (Arias, González, Prada, et al., 2015; Barcelos, 1998; Ghesquière, Barcelos, Santos, & Amblard, 1987; Moretzsohn et al., 2002). More recently, new studies have applied microsatellite markers (SSRs) to study genetic and phenotypic diversity and population structure, and even to establish core collection (CC) of the American and African oil palms (Arias, González, Prada, et al., 2015; Arias, González, & Romero, 2015; Bakoumé et al., 2015; Chee Chun et al., 2018; Khomphet, Eksomtramage, & Duangpan, 2018; Natawijaya et al., 2019; Zhou, Xiao, Xia, & Yang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PCA is a multivariate tool analysis, which helps to obtain at the same time component groups with more important traits. This approach was widely implemented by several other plant scientists for specific breeding [16][17][18][19][20]. In this study, PCA revealed that the first three principal components (PC) with eigenvalue greater than 1, accounted for 90.55% variation within the 25 progenies ( Table 4).…”
Section: Resultsmentioning
confidence: 85%